“Madness” in Singapore : perception and treatment towards the other (late 19th to mid-20th century) - Wang, Jing Wen (2019)
In this paper, I examine how societal perception and medical treatment towards mental illness from the late nineteenth to the mid-twentieth century weighed under colonial influences. Existing historiography of mental illness in colonial Singapore has focused on institutional development, dismissing the stories of those deemed ‘mad’. This paper identifies periodicals, legal cases, and oral interviews to build a clear and compelling narrative of how mental unsoundness was perceived. Societal perception laid the fundamentals to the development of medicine for ‘madness’. Further discerning the clinical notion of madness by examining the voices of medical personnel, the interaction between Western-taught doctors and native practitioners will be highlighted. With British decolonization of Singapore, medicine became increasingly focused on healing the mind and body. Juxtaposing against the earlier antagonistic seclusion of mental illness, an overall positive development by the mid-twentieth century brought about a betterment of the mental illness environment. On the whole, an amalgamation of colonial prejudice, collective societal repugnance towards the mad, and slow medicinal development culminated in a complex ‘madness’ discourse of colonial Singapore. Remnants of this colonial past continue to manifest in the discourse of mental illness today.